Nonlabeling and quantitative assessment of chondrocyte viability in articular cartilage with intrinsic nonlinear optical signatures. Issue 4 (February 2020) - Li, Yang; Chen, Xun; Watkins, Beckham; Saini, Neal; Gannon, Steven; Nadeau, Elizabeth; Reeves, Russell; Gao, Bruce; Pelligrini, Vincent; Yao, Hai; Mercuri, Jeremy; Ye, Tong
Chondrocyte viability is a crucial factor for evaluating cartilage health. Most prevalent cell viability assays rely on dyes and are not applicable for in vivo or longitudinal studies. Here we demonstrated that the two-photon excited autofluorescence and second harmonic generation microscopy provided high-resolution imaging of cartilage tissue and distinguished live/dead chondrocytes by visual assessment. Furthermore, the normalized autofluorescence ratio was proposed as a quantitative indicator to determine chondrocyte viability. Based on the indicator, a curve fitting and simulated receiver operating characteristic method was proposed to identify the live/dead cell populations as well as the indicator threshold without dye labeling. Thus, it established the label-free imaging method for chondrocyte viability assay in cartilage tissue. Impact statement: Chondrocytes are the only cellular component found in the cartilage, playing a critical role in maintaining the homeostasis of articular cartilage. The viability of chondrocytes is a crucial factor for evaluating cartilage health. However, the current prevalent cell viability assays rely on dye staining and thereby are not applicable in vivo or in longitudinal assessments. In this study, we demonstrate that the intrinsic signals such as two-photon excited autofluorescence and second harmonic generation can be used to classify live and dead chondrocytes in cartilage tissue. A quantitative measure is also proposed allowing development of automated assessment algorithms. The nonlabeling nature of this method suggests the potential applicability to nondestructive and in vivo assessment of cartilage health.